2022
DOI: 10.2147/nss.s369192
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of White Matter Integrity Changes in the Anterior Cingulum Among Shift Workers: A Cross-Sectional Study

Abstract: Introduction We investigated the white matter integrity in shift and non-shift workers and its associations with sleep and activity. Methods Diffusion tensor imaging (DTI) was performed on 61 shift workers and 31 non-shift workers. Their sleep and activity profiles were assessed using the Pittsburgh Sleep Quality Index (PSQI), sleep diaries, and actigraphy. Fractional anisotropy (FA) (a measure of white matter integrity) was calculated using DTI tractography. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…For example, Cullen et al (2020) examined the associations between FA across numerous tracts and several dimensions of depression (e.g., lassitude, appetite changes, traumatic intrusion) in adolescents with depression and found that greater right CGC FA was associated with greater lassitude, which is characterized by feelings of exhaustion, low energy, sleepiness, difficulty getting going, and feeling worse in the morning ( Cullen et al, 2020 ). In a study with adults, Lee et al (2022) found that shift-workers, who regularly experience sleep disturbances due to the desynchronization of their circadian rhythm and homeostatic sleep pressure, exhibited greater right CGC FA than did non-shift-workers. Moreover, in shift-workers, greater right CGC FA was positively correlated with multiple indices of poor sleep quality, including poorer subjective sleep, whereas the opposite pattern (higher CGC FA, better sleep quality) was observed in non-shift-workers.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Cullen et al (2020) examined the associations between FA across numerous tracts and several dimensions of depression (e.g., lassitude, appetite changes, traumatic intrusion) in adolescents with depression and found that greater right CGC FA was associated with greater lassitude, which is characterized by feelings of exhaustion, low energy, sleepiness, difficulty getting going, and feeling worse in the morning ( Cullen et al, 2020 ). In a study with adults, Lee et al (2022) found that shift-workers, who regularly experience sleep disturbances due to the desynchronization of their circadian rhythm and homeostatic sleep pressure, exhibited greater right CGC FA than did non-shift-workers. Moreover, in shift-workers, greater right CGC FA was positively correlated with multiple indices of poor sleep quality, including poorer subjective sleep, whereas the opposite pattern (higher CGC FA, better sleep quality) was observed in non-shift-workers.…”
Section: Discussionmentioning
confidence: 98%
“…Regarding white matter integrity, shift workers exhibited higher fractional anisotropy (FA) values in the bilateral anterior cingulum compared with non-shift workers; increased FA in the right anterior cingulum was correlated with poor sleep quality [39]. A resting-state fMRI study showed that shift workers exhibited altered functional connectivity in the salience network.…”
Section: Neural Correlates Of Emotional Dysregulation Among Shift Wor...mentioning
confidence: 99%
“…Moreover, grey matter alterations in the left postcentral gyrus mediated the influence of sleep disturbance on the depressive symptoms of the subjects. Another study (Lee et al., 2022 ) compared the differences in white matter structure of shift workers and non‐shift workers, finding that the shift workers exhibited higher fractional anisotropy in the bilateral anterior cingulum, and that the increased fractional anisotropy in the right anterior cingulum was correlated with the poor sleep quality of shift workers. These studies provided preliminary knowledge of shift work affecting the brain structural plasticity of workers, which was generally attributed to the shift work‐induced sleep deprivation and the resulting disruption of the internal environment.…”
Section: Introductionmentioning
confidence: 99%